2018
DOI: 10.4103/ua.ua_120_17
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of ultrasonographical findings of hydronephrosis/atrophy with 99m technetium-dimercaptosuccinic acid in childhood: A single-center experience from Turkey

Abstract: Introduction:To assess the association of frequently detected abnormalities (hydronephrosis and/or atrophy) on renal ultrasound with dimercaptosuccinic acid (DMSA) scan and the impact of vesicoureteral reflux (VUR) on these abnormalities to find new perspectives in pediatric age group.Materials and Methods:We retrospectively reviewed the DMSA, ultrasonography (US), micturating cystourethrography (MCUG) findings, and medical records of pediatric patients with hydronephrosis and/or atrophy who were at follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In the present study, according to ultrasound and/or MRU findings, 14 out of 50 (28%) patients had atrophic changes, 18 out of 50 (36%) patients had mild to moderate hydronephrosis, 13 out of 50 (26%) patients had marked hydronephrosis and 5 out of 50 (10%) patients had both atrophic changes and hydronephrosis. This disagreed with Kandur, et al [10] who reported that 72 out of 148 (48.6%) patients had atrophic changes, 36 out of 148 (24.3%) patients had mild to moderate hydronephrosis, 30 out of 148 (20.3%) patients had marked hydronephrosis and 10 out of 148 (6.8%) patients had both atrophic changes and hydronephrosis. This disagreement may be attributed to difference in number of patients included in the studies.…”
Section: Discussionmentioning
confidence: 62%
“…In the present study, according to ultrasound and/or MRU findings, 14 out of 50 (28%) patients had atrophic changes, 18 out of 50 (36%) patients had mild to moderate hydronephrosis, 13 out of 50 (26%) patients had marked hydronephrosis and 5 out of 50 (10%) patients had both atrophic changes and hydronephrosis. This disagreed with Kandur, et al [10] who reported that 72 out of 148 (48.6%) patients had atrophic changes, 36 out of 148 (24.3%) patients had mild to moderate hydronephrosis, 30 out of 148 (20.3%) patients had marked hydronephrosis and 10 out of 148 (6.8%) patients had both atrophic changes and hydronephrosis. This disagreement may be attributed to difference in number of patients included in the studies.…”
Section: Discussionmentioning
confidence: 62%